Comparisons of the English and Chinese Language Networks: Many Similarities and Few Differences (Communications in Computational Physics, 2010)
With words as nodes, and a link exits between two neighboring words, theweighted directed English and Chinese written human language networks are constructedfrom one English novel and two Chinese ones. We hereby analyze in detailthe topological structure of them, in order to clarify their similar and different statisticalproperties. The empirical results show that the English and Chinese languagenetworks all possess the shifted power law (SPL) degree distribution, the small-worldproperty and the hierarchical structure, the connections among the words have positiveassortativity coefficient and reciprocal characteristics. We also investigate the featuresof the strength and the centrality, which describe the importance of a specificword. Furthermore, considering the growth properties of the language networks andpart of topological property, we find that the English written human language networkgrows slower than the Chinese one, which implies different mechanisms of the Englishand Chinese languages.